THE ROLE OF ANTIBIOTHERAPY IN THE ORAL REHABILITATION OF THE PERIODONTAL AFFECTED PATIENT - Mihaela Moisei; Liliana Pasarin; Sorina Solomon; Cornelia Oanta; Diana Tatarciuc; Irina Ursarescu; Silvia Martu (Romanian Journal of Oral Rehabilitation, 2015)
The periodontal disease is one of the most frequent chronic diseases and one of the most common microbial infections in the adult patient. It appears as a consequence of the interaction between the pathogenic bacteria (periodontal pathogens) with a susceptible host. The main objective of the therapeutic management is to obtain a high standard of oral hygiene and to prevent the loss of periodontal attachment by mechanical and surgical methods. The adjunctive drug therapy demonstrated in time clinical and microbiologic advantages, with an essential role for the antibiotics. The antibiotic intake can present a therapy role when it is addressed to the microorganisms from the red complex maintained in the periodontal tissues after the mechanical debridement or in recurrent sites from localized aggressive periodontal disease. They are also necessary in cases of acute forms of the disease, ANUG or ANUP, aggressive and refractory to the periodontal treatment. The prophylaxis with antibiotics is justified in situations like the ones that require the use of membranes and also to avoid the risk for bacteraemia in patients with systemic impairment. The selection of the type of antibiotic and of the administration method (local or systemic) is performed according to the clinical form and to the type of microorganism, to the antibiogram, to the drug history of the patients and to his systemic status.